HASIL PERBEDAAN DAN AKTIVITAS BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR AND SHARE DAN DECISION MAKING - Husnarika Febrianti; Khairuna; Chissy (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
This study aims to determine the differences in student learning outcomes using the Think Pair And Share and Decision Making learning models on the subject matter of the Human Movement System in class VIII MTs BIMA in the 2020/2021 academic year. This research is a quantitative research, with the type of quasi-experimental research (quasi-experimental). The population is all students of class VIII MTs BIMA, the sample of this research is 36 students of class VIII-A and 36 students of class VIII-B. Data analysis was performed by t-test. These findings indicate that: (1) student learning outcomes using the Think Pair And Share learning model are better with an average score of 84,848 than student learning outcomes using the Decision Making model with an average score of 79.88. (2) There is a significant difference in student learning outcomes with the Think Pair And Share and Decision Making learning models on the subject matter of the human movement system in class VIII MTs BIMA for the 2020/2021 school year. This is in accordance with the t-test calculation, that based on the calculation results obtained tcount = 2.39 this result is compared with ttable at the real level = 0.05, t table = 1.67 then t count > t table = 2.39 > 1.67. The conclusion of this study explains that there are significant differences in student learning outcomes using the Think Pair And Share and Decision Making learning models on the subject matter of the human movement system in class VIII MTs BIMA in the 2020/2021 school year.